Altered brain network organization in adults with Asperger's syndrome: decreased connectome transitivity and assortativity with increased global efficiency - Javaheripour, Nooshin; Wagner, Gerd; de la Cruz, Feliberto; Walter, Martin; Szycik, Gregor R.; Tietze, Fabian-Alexander (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder, which persists into adulthood with both social and cognitive disturbances. Asperger's syndrome (AS) was a distinguished subcategory of autism in DSM-IV-TR defined by specific symptoms including difficulties in social interactions, inflexible thinking patterns and repetitive behaviour without any delay in language or cognitive development. Studying the brain functional organization of individuals with these specific symptoms may help to better understand Autism spectrum symptoms. The aim of this study is therefore to investigate functional connectivity as well as functional network organization characteristics using graph-theory measures of the wholebrain in male adults with AS compared to healthy controls (HC) (AS: n = 15, age range 21 -55 (mean ± sd: 39.5 ± 11.6), HC: n = 15, age range 22 -57 (mean ± sd: 33.5 ± 8.5)). No significant differences were found when comparing the region-by-region connectivity at the whole-brain level between the AS group and HC. However, measures of "transitivity," which reflect local information processing and functional segregation, and "assortativity," indicating network resilience, were reduced in the AS group compared to HC. On the other hand, global efficiency, which represents the overall effectiveness and speed of information transfer across the entire brain network, was increased in the AS group. Our findings suggest that individuals with AS may have alterations in the organization and functioning of brain networks, which could contribute to the distinctive cognitive and behavioural features associated with this condition. We suggest further research to explore the association between these altered functional patterns in brain networks and specific behavioral traits observed in individuals with AS, which could provide valuable insights into the underlying mechanisms of its symptomatology.